Invasive pneumococcal disease (IPD) in HIV infected patients in Israel since the introduction of pneumococcal conjugated vaccines (PCV): Analysis of a nationwide surveillance study, 2009-2014 - Michal Chowers; Gili Regev-Yochay; Orna Mor; Ronit Cohen-Poradosu; Klaris Riesenberg; Oren Zimhony; Daniel Chemtob; Michal Stein; Ron Dagan; Itzchak Levy (Taylor & Francis Group, 2017)
Study aim: to assess the incidence, risk factors and outcome of invasive pneumococcal disease (IPD) among the Israeli HIV population. A matched case-control study nested in a nationwide, prospective, population-based, cohort of adult IPD was performed. In addition, the HIV-IPD patients were compared to the general adult HIV population in Israel. Study period: from the introduction of PCV into the national immunization program (NIP) in July 2009 to June 2014. Each HIV patient within the IPD cohort was matched to 4 non-HIV controls. Serotyping was performed by a central laboratory using the Quellung reaction. Thirty-five IPD episodes in 33 HIV patients were identified, with a median annual incidence of 128/100,000 HIV+ persons compared to 5.1/100,000 in the age-matched, non-HIV population. Compared to the general HIV population, HIV-IPD patients practiced intravenous drug use more frequently and originated from a country with generalized epidemic (OGE), mainly non-citizens lacking medical insurance. The proportion of men who have sex with men (MSM) was lower than in the general HIV population. Pneumonia was the most common clinical presentation (81%), while meningitis occurred in only one patient. Outcomes were similar to those of the IPD non-HIV population. Nineteen serotypes were identified, of which only 42% were covered by PCV13 vaccine. By 2014, none of the HIV-IPD cases belonged to serotypes covered by PCV13. In conclusion, most HIV IPD cases were from marginalized populations with poor access to health services. A decrease in IPD cases covered by PCV 13 was observed.